Recent brachiopods from north-western Australia - Bitner, Maria Aleksandra (Zootaxa, 2025)
Nine brachiopod species belonging to eight genera have been identified in the material from north-western Australia, including Christmas Island. Three species, i.e. Lingula anatina Lamarck, Thecidellina blochmanni Dall, and Frenulina sanguinolenta (Gmelin) have been previously reported from this region. The dominant species in the studied material is the endemic Australian species Jaffaia jaffaensis (Blochmann), which is well known from southern Australia but recorded here for the first time from northern Australia. The remaining species, Dysedrosia borneoensis (Dall), Dallithyris murrayi Muir-Wood, Terebratulina callinome Dall, T. photina Dall, and Jolonica hedleyi Dall are the first records of these species from off Australia. The assemblage from north-western Australia differs markedly in species composition from the brachiopod fauna of southern and eastern Australia and shows affinities to the Indo-NW Pacific brachiopods.